Analysis of Data Dissemination and Use Practices in the Health Sec-tor in Tanzania: Results of desk review and interviews with key stakeholders - Darcy, Niamh M; Somi, Geoffrey; Matee, Mecky; Wengaa, Desderi; Perera, Sriyanjit (Journal of Health Informatics in Africa, 2017)
Many developing countries have included improving data use as part of their overall health sector strategy, usually included as part of their Monitoring and Evaluation section.  Tanzania decided to develop a more comprehensive data dissemination and use strategy, based on primary research to understand the challenges and opportunities that exist to improve evidence based decision making at all levels of the health system.  The first paper presents the methodology used to develop the Data Dissemination and Use (DDU) strategy.  The second paper focuses on the results from the DDU research. The third paper focuses on how the results were used to develop the national DDU strategy.  This is the second paper which shows the results from the DDU research.